Effect of Opaque Porcelain Thickness Bond Strength of Porcelain to Ni-Cr Alloys - Hadi, Alireza; Massoumi, Farhood; Mossaei, Akram (Journal of Dental School, 2019)
Objectives: Metal-ceramic restorations are the standard by which all esthetic restorations are measured. Fracture of dental restorations is a multifactorial problem, which is serious and costly. Debonding of porcelain from the metal substructure and the bond strength depend on many factors. The purpose of this study was to determine whether the opaque porcelain thickness has a significant effect on metal ceramic bond strength utilizing the ISO 9663 standard crack initiation test. Methods: Thirty rectangular Ni-Cr metal bars (25×5×0.3mm) were fabricated according to ISO9663 standards. The metal bars were divided into three groups of 10. Opaque, body and enamel Noritake porcelain were applied on the middle of the bar according to ISO9663 standards up to 1mm porcelain thickness. The opaque porcelain thicknesses were 0.1, 0.2, and 0.3 mm, respectively in the three groups. The 3-point bending test was applied according to the ISO9663 standards and fracture strength (Ffail) was measured using a universal testing machine with a crosshead speed of 1.5mm/minute. Results: Analyses of the data by one-way ANOVA demonstrated no significant differences in bond strength among the three experimental groups (P=0.26). Conclusion: Within the limitations of this study, it is concluded that 0.1mm opaque porcelain provides sufficient bond strength between metal and ceramic in metal-ceramic restorations.